UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE SKRIP SISWA KELAS II SDN 016 BULUH KASAP DUMAI TIMUR - Robiati Robiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
The background of this research is the learning process is still centered on the teacher, the lesson using thelecture method, so that the students are less motivated in the learning process, the students are less enthusiasticand not actively inquiring in the delivery of learning materials. This study aims to improve teacher skills andstudent activities so as to improve student learning outcomes of grade II SDN 016 Buluh Kasap Dumai Timurusing cooperative learning model Scripts. This research is a classroom action research conducted in May 2012,the subject of this research is the second grader of SDN 016 Buluh Kasap Dumai Timur with amount of 33.Measuring tool used in this research is teacher activity, student activity, learning result, and mastery learning.The result showed that: (a) on the basic score of students who reached KKM 14 students (42.42%), UH I was 24students (72,72) and UH II was 29 students (87,87%) ; and (b) the result of learning mathematics of studentshave an increase on base score equal to 54,60 with low category, at UH I equal to 68,20 with medium category,and at UH II equal to 77,20 with high category. Based on the results of this study, it can be concluded thatcooperative learning model type of script can improve the learning outcomes of students of grade II SDN 016Buluh Kasap Dumai.